Pengaruh Gaya Hidup Konsumtif terhadap Perilaku Keuangan dan Kecenderungan Penggunaan Pinjaman Online di Era Digital - Marisa Jahra Salsabila; Rifa Aqilah Sugandi; Naia Kaiela Kriska Davina; Muhammad Brian Aryawinata; Muhammad Razzaqqa Dhaffin; Tsaqiif Muhammad Rizqy (Pancasila and Civics Education Journal (PCEJ), 2026)
Abstract: The development of digital technology has driven changes in people's consumption patterns and influenced individual financial behavior. Ease of access to social media, e-commerce, and financial technology services has contributed to the emergence of a consumptive lifestyle that has the potential to increase the use of online loans. This study aims to analyze the influence of a consumptive lifestyle on financial behavior and the tendency to use online loans in the digital era. The study used a literature review method with a qualitative descriptive approach. Data were obtained from various literature sources, including journal articles, academic books, official agency reports, and relevant scientific publications. The analysis was conducted through identification, comparison, and synthesis of various research findings regarding a consumptive lifestyle, financial behavior, and the use of online loans. The results of the study indicate that a consumptive lifestyle influences the decline in the quality of financial behavior, such as poor ability to manage expenses, save, and plan finances. Furthermore, a consumptive lifestyle increases the tendency to use online loans as an alternative financing option to meet consumption needs. This condition has the potential to cause financial problems, financial stress, and debt dependence. Therefore, strengthening financial literacy is a crucial step in encouraging healthier and more responsible financial behavior.Keywords: Consumptive Lifestyle, Financial Behavior, Online Loans, Financial Literacy, Digital EraAbstrak: Perkembangan teknologi digital telah mendorong perubahan pola konsumsi masyarakat dan memengaruhi perilaku keuangan individu. Kemudahan akses media sosial, e-commerce, serta layanan teknologi finansial turut mendorong munculnya gaya hidup konsumtif yang berpotensi meningkatkan penggunaan pinjaman online. Penelitian ini bertujuan untuk menganalisis pengaruh gaya hidup konsumtif terhadap perilaku keuangan dan kecenderungan penggunaan pinjaman online di era digital. Penelitian menggunakan metode kajian pustaka dengan pendekatan deskriptif kualitatif. Data diperoleh dari berbagai sumber literatur berupa artikel jurnal, buku akademik, laporan lembaga resmi, dan publikasi ilmiah yang relevan. Analisis dilakukan melalui identifikasi, perbandingan, dan sintesis berbagai temuan penelitian mengenai gaya hidup konsumtif, perilaku keuangan, dan penggunaan pinjaman online. Hasil kajian menunjukkan bahwa gaya hidup konsumtif berpengaruh terhadap menurunnya kualitas perilaku keuangan, seperti rendahnya kemampuan mengelola pengeluaran, menabung, dan merencanakan keuangan. Selain itu, gaya hidup konsumtif meningkatkan kecenderungan penggunaan pinjaman online sebagai alternatif pembiayaan untuk memenuhi kebutuhan konsumsi. Kondisi tersebut berpotensi menimbulkan masalah keuangan, stres finansial, dan ketergantungan utang. Oleh karena itu, penguatan literasi keuangan menjadi langkah penting dalam mendorong perilaku keuangan yang lebih sehat dan bertanggung jawab.Kata Kunci: Gaya Hidup Konsumtif, Perilaku Keuangan, Pinjaman Online, Literasi Keuangan, Era Digital